Partial purification and characterization of pectin methylesterase from orange (Citrus sinensis) cv. Pera-rio - Do Amaral, S. H.; De Assis, S. A.; Oliveira, OMMD (Blackwell Publishing, 2005)
The enzyme pectin methylesterase (PME) from orange was extracted and partially purified by filtration on Sephadex G-100. The extraction buffer for orange PME was borate-acetate containing 0.4 M NaCl. Orange PME showed optimum pH at 8.0 and optimum temperature at 50C. The PME enzyme was completely inactivated after 1 min of incubation at 90C. The specific activity increased in the presence of 0.15 M NaCl or 0.025 M Na2SO4, 0.10 M KCl, 0.025 M K2SO4, 0.05 and 0.1 M NH4Cl. Lithium chloride and Li(2)SO(4)inhibited the enzymatic activity at all concentrations studied. The K-m and V(max)value of PME were 0.36 mg/mL and 5.26 mu mol/mL-mg protein, respectively.